Formulation of Pseudomonas chlororaphis strains for improved shelf life - Correa, E. B. [UNESP]; Sutton, J. C.; Bettiol, Wagner [UNESP] (Elsevier B.V., 2015)
Formulations of Pseudomonas strains with long-term shelf life are needed for commercial use in biological disease control and growth promotion in crops. In the present work Pseudomonas chlororaphis (Pc) 63-28 formulated with coconut fiber [moisture content (MC) of 80%], talc (MC 8%) or peat (MC 40%), with or without the addition of carboxymethylcellulose or xanthan gum, and formulations of Pc 63-28 and P. chlororaphis TX-1 in coconut fiber with water contents (v:v) of 75%, 45%, and 25%, were evaluated in terms of shelf life and cell viability. The shelf life of Pc 63-28 was longer when formulated in coconut fibre with a MC was 80% than in the other formulations and longer at 3 +/- 1 degrees C compared to 22 +/- 1 degrees C. Densities of viable Pc 63-28 cells in coconut fiber stored at 3 +/- 1 degrees C did not decline significantly during 224 days when the MC was 80% and within 120 days at 75% MC. Densities of Pc TX-1 in coconut fiber of 75% MC did not decline within 60 days at 3 +/- 1 degrees C. P. chlororaphis 63-28 survived longer in deionized water and buffer than in canola oil. Cells of Pc 63-28 cells formulated in coconut fibre of 80% MC after storage for 140 days at 3 +/- 1 degrees C in coconut fiber improved hydroponic growth of hydroponic lettuce and better than cells freshly recovered from culture. We conclude that coconut fiber is a carrier of superior performance in maintaining shelf life of Pseudomonas strains. The observed shelf life would be sufficient for practical use of Pseudomonas strains as tools for disease control and growth promotion in crops. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Bioagents; Coconut fiber; Lactuca sativa; Bacterial formulation